The Red Vienna sourcebook - McFarland, Rob; Zechner, Ingo; Spitaler, Georg (Camden House, 2020)
An encyclopedic selection of original documents from the Austrian capital's pathbreaking, progressive interwar period, translated and with contextualizing introductions and commentaries.
Title from publisher's bibliographic system (viewed on 29 Oct 2020)
Keywords: Vienna (Austria) -- Sources -- History -- 20th century; Vienna (Austria) -- Sources -- Social policy; Quelle; Ideengeschichte 1919-1934; Wien; Geschichte 1919-1934